Climate Change, Religion and Education: Exploring Influence of Faith-Based Leadership on Environmental Sustainability - Aji Mardani, Dede; Siti Masuroh, Imas (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aims to examine the role of religious leaders in climate change education in Tasikmalaya through an Islamic approach, with a focus on the use of religious teachings to convey environmental messages and their effectiveness in increasing public awareness and participation. Novelty: This study combines religion with environmental education, making Islamic teachings the basis for environmentally friendly behavior, and highlighting unique practices such as metaphorical narratives and environmentally nuanced worship activities, such as